Newer Frontiers in Urology - Sriram Krishnamoorthy (Newer Frontiers in Urology, Edition 1, 2025)
The field of urology is undergoing a rapid evolution, shaped by groundbreaking research, innovative technologies, and a deeper understanding of patient-centred care. Newer Frontiers in Urology presents a comprehensive exploration of these transformative developments, offering readers an invaluable resource that bridges current practices with future possibilities. This book delves into cutting-edge topics such as minimally invasive surgical techniques, advancements in imaging modalities, and the growing role of artificial intelligence in diagnostics and treatment planning. Key chapters address emerging therapies for challenging urological conditions, including genitourinary cancers, urinary tract infections, and stone disease. Contributions from leading experts highlight the integration of precision medicine, biomarkers, and genetic insights into personalized patient care. The text also considers the global impact of urological diseases, emphasizing equity in access to innovations and the need for collaborative international efforts. By combining rigorous scientific analysis with practical applications, Newer Frontiers in Urology serves as an essential guide for clinicians, researchers, and healthcare professionals eager to stay at the forefront of their field. With its focus on innovation and patient outcomes, this volume inspires a forward-thinking approach to urology, underscoring the discipline’s potential to improve lives worldwide.